Hedgehog-induced phosphorylation by CK1 sustains the activity of Ci/Gli activator. - Shi, Q.; Li, S.; Li, S.; Jiang, A.; Chen, Y.; Jiang, J. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Hedgehog (Hh) signaling governs many developmental processes by regulating the balance between the repressor (Ci(R)/Gli(R)) and activator (Ci(A)/Gli(A)) forms of Cubitus interruptus (Ci)/glioma-associated oncogene homolog (Gli) transcription factors. Although much is known about how Ci(R)/Gli(R) is controlled, the regulation of Ci(A)/Gli(A) remains poorly understood. Here we demonstrate that Casein kinase 1 (CK1) sustains Hh signaling downstream of Costal2 and Suppressor of fused (Sufu) by protecting Ci(A) from premature degradation. We show that Hh stimulates Ci phosphorylation by CK1 at multiple Ser/Thr-rich degrons to inhibit its recognition by the Hh-induced MATH and BTB domain containing protein (HIB), a substrate receptor for the Cullin 3 family of E3 ubiquitin ligases. In Hh-receiving cells, reduction of CK1 activity accelerated HIB-mediated degradation of Ci(A), leading to premature loss of pathway activity. We also provide evidence that Gli(A) is regulated by CK1 in a similar fashion and that CK1 acts downstream of Sufu to promote Sonic hedgehog signaling. Taken together, our study not only reveals an unanticipated and conserved mechanism by which phosphorylation of Ci/Gli positively regulates Hh signaling but also provides the first evidence, to our knowledge, that substrate recognition by the Cullin 3 family of E3 ubiquitin ligases is negatively regulated by a kinase.